Pathogenic and biochemical variability in Fusarium udum, causing Pigeonpea wilt - and J.P. SRIVASTAVA, VINOD KUMAR*, V.B. CHAUHAN and (Indian Phytopathology, 2007)
Study was conducted to find out the extent of pathogenic and biochemical variability among the 11 isolates of Fusarium udum collected from Uttar Pradesh, New Delhi and Hyderabad. On the basis of morphological characters and wilt incidence, 104 isolates were grouped into three clusters in SPSS analysis. Wilt incidence ranged from 13% to 100%. Cell biomolecular composition viz., total sugars, total proteins and amino acids varied highly and most aggressive isolate was found to be rich in total sugar content. Isolates varied in enzyme and fusaric acid production. No correlation existed among the isolates with respect to enzyme activity.